(untitled) (Journal of Information Technologies in Education (ITE), 2015)
MATLAB-programs of some discrete random event has been developed and intended (1) as an exercise at the study of Algorithmization and Programming Course, and (2) for carrying out some "experiments" by lecturing the Course of Probability and Statistics Theory, or at its self-study by students. The programs allows to do several probabilistic experiments in a necessary amount M,using the random number generator, to count up frequency of "favorable events" appearance and compare it to theoretical probability. This displays the Law of large numbers, i.e. approaching experimental results to theory with unlimited increase of М. The work, however, lies not only in this pragmatic result. It should encourage students to study problems of Probability Theory by means of creation appropriate computer codes. The most easy and quick way to this leads to MATLAB-environment. That is why the paper suggests principles of programming in it along with creation of graphical user interface (GUI).